2014
DOI: 10.1007/s00467-014-2760-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of clinical pharmacy services in a pediatric dialysis unit

Abstract: Pharmacist-initiated pharmaceutical care improved the satisfaction and biochemical findings of patients on hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Pediatric pharmacists can improve care for the nearly 10 000 pediatric ESKD patients in the U.S. A randomized study of 50 hemodialysis pediatric patients showed that pharmacist‐based care improved blood pressure, phosphorus, parathyroid hormone, and calcium‐phosphate product compared with usual care 53 . Importantly, pharmacist‐based care also improved patient satisfaction.…”
Section: Opportunities For Pharmacists To Integrate Into the Care Of mentioning
confidence: 99%
“…Pediatric pharmacists can improve care for the nearly 10 000 pediatric ESKD patients in the U.S. A randomized study of 50 hemodialysis pediatric patients showed that pharmacist‐based care improved blood pressure, phosphorus, parathyroid hormone, and calcium‐phosphate product compared with usual care 53 . Importantly, pharmacist‐based care also improved patient satisfaction.…”
Section: Opportunities For Pharmacists To Integrate Into the Care Of mentioning
confidence: 99%
“…poprawę parametrów biochemicznych (np. stężenia fosforanów, wapnia, ferrytyny, parathormonu) i jakości życia w porównaniu z grupą kontrolną [19,20]. Również u dzieci leczonych warfaryną lepszą kontrolę INR obserwowano w grupie pacjentów, których farmakoterapia nadzorowana była przez farmaceutę klinicznego [21].…”
Section: Zapobieganie Występowaniu Błędów Lekowychunclassified
“…Many medical specialities with complex conditions that require polytherapy of potentially toxic medications routinely include clinical pharmacists on ward rounds or in outpatient clinics. 25 Studies have evaluated the impact of clinical pharmacist involvement with outcome measures including symptom-control, monitoring of blood indices and patient satisfaction. Statistically significant improvements in some aspects of patient management have been seen with more pharmacist intervention or integration within the clinical team.…”
Section: Scales For Assessing Potential Harm Secondary To Prescribingmentioning
confidence: 99%